High-frequency repetitive transcranial magnetic stimulation to the left dorsolateral prefrontal cortex of patients with Parkinson's disease and treatment-resistant depression: a pilot study. Issue 3 (4th July 2019) - Randver, René; Davel, Külli; Toomsoo, Toomas
ABSTRACT: An increasing amount of evidence is showing the therapeutic effects of rTMS on PD-related non-motor functions neuroanatomically linked to the DLPFC. This presents an ongoing need to apply an optimal combination of stimulation parameters to clinically heterogeneous patient populations, including those with neuropsychiatric problems and other comorbidities along with the neurodegenerative process. In this prospective pilot study, six patients with PD and treatment-resistant depression were thoroughly assessed and carefully monitored before, during, and after each stimulation procedure. The results can provide the basis for developing an extended rTMS protocol that is both effective and safe.